Synthesis and characterization of a glycerol salicylate resin for bioactive root canal sealers. (2nd July 2013) - Portella, F. F.; Santos, P. D.; Lima, G. B.; Leitune, V. C. B.; Petzhold, C. L.; Collares, F. M.; Samuel, S. M. W.
Abstract Aim To develop and characterize a salicylate resin with potential use in bioactive endodontic sealers. Methodology Methyl salicylate, glycerol and titanium isopropoxide were added in a closed system for the transesterification reaction. The resin obtained was characterized by proton nuclear magnetic resonance spectroscopy (1H NMR) and size exclusion chromatography (SEC). To verify the applicability of the resin to the development of endodontic sealers, experimental cements were prepared by mixing glycerol salicylate resin, calcium hydroxide and methyl salicylate in the ratios of 2 : 1 : 1, 1 : 2 : 1, 1 : 1 : 2, 1 : 1 : 1, 4 : 1 : 1, 1 : 4 : 1 and 1 : 1 : 4. Setting times were measured according to ISO 6876. Features of the hardening reaction were described by micro‐RAMAN spectroscopy. Results The transesterification reaction had a 72% efficiency. The 1H NMR analysis revealed the presence of the expected functional groups (hydroxyls and aromatic rings), and the SEC confirmed the molar mass of the resin produced. The setting times of experimental sealers ranged from 70 min (ratio 1 : 1 : 1) to 490 min (ratio 1 : 1 : 4). The conversion of the salicylic groups (1 613 cm−1) to salicylate salt (1 543 cm−1) and the reduction in calcium hydroxide peaks (1084 and 682 cm−1) were confirmed by micro‐RAMAN spectroscopy, which showed the calcium chelation by the resin. Conclusion The new glycerol salicylate resin was successfully synthesized and revealed a potential application in the development of endodontic sealers.